Soil seed bank pattern of Adesmia tristis Vogel from Campos de Cima da Serra ecosystem in southern Brazil - Ferreira, Nadilson Roberto; Franke, Lucia Brandão; Blochtein, Betina (Iheringia, Série Botânica., 2016)
This study evaluated the soil seed bank (SSB) of Adesmis Tristis Vogel, plant deaths in the ecosystem, the interference of the soil potential acidity on the SSB and a seedling survey in situ. After simulating SSB in levels of acidity and surveying seedlings of A. tristis in plots, we confirmed that A. tristis naturally reseeds; with an aggregated or random distribution depending on the cutting management; the soil potential acidity reduces the activation of A. tristis SSB; the establishment of new individuals requires openings in the environment due to the death of mother plants.